OLFACTORY ORGAN AND ITS SEXUAL DIMORPHISM IN THE ELECTRIC RAY, NARCINE TIM LEI (DAY) - Waghray, Sarala (Indian Journal of Fisheries, 2011)
The olfactory organ of the electric ray, Narcine timlei (Day), exhibits sexual dimoi’phism. The olfactory organ, almost kidney shaped is more rounded in male, while in female it is slightly elongated and narrow. The linguiform process of lamella is more prominent in the males than in females. The olfactory organ in the embryo is also dealt with.